2013
DOI: 10.3168/jds.2012-6168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding algal meal high in docosahexaenoic acid on feed intake, milk production, and methane emissions in dairy cows

Abstract: This study examined effects on milk yield and composition, milk fatty acid concentrations and methane (CH4) emissions when dairy cows were offered diets containing different amounts of algal meal. The algal meal contained 20% docosahexaenoic acid (DHA) and cows were offered either 0, 125, 250, or 375 g/cow per d of algal meal corresponding to 0, 25, 50, or 75 g of DHA/cow per d. Thirty-two Holstein cows in mid lactation were allocated to 4 treatment groups, and cows in all groups were individually offered 5.9k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
98
3
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 46 publications
27
98
3
9
Order By: Relevance
“…The positive impact of Spirulina platensis on milk yield was also confirmed by the study conducted by Šimkus et al [52]. Other studies conducted elsewhere however found no effect of feeding algal-based diet on milk yield [53][54][55][56] (Table 3).…”
Section: Peiretti and Meineri [11] Rabbitsupporting
confidence: 77%
“…The positive impact of Spirulina platensis on milk yield was also confirmed by the study conducted by Šimkus et al [52]. Other studies conducted elsewhere however found no effect of feeding algal-based diet on milk yield [53][54][55][56] (Table 3).…”
Section: Peiretti and Meineri [11] Rabbitsupporting
confidence: 77%
“…In the present study the form of algae supplementation was protected similarly to that used by Stamey et al (2012). Similarly, Moate et al (2013), offering different amounts of algal meal to lactating cows, found no alterations on milk yield although milk fat yield decreased with the addition of DHA. On the contrary, other authors (Franklin et al, 1999;Boeckaert et al, 2008;Hostens et al, 2011), supplementing cows with unprotected marine algae observed a reduction in dry matter intake (DMI) and milk yield.…”
Section: Milk Production and Fatty Acid Compositionmentioning
confidence: 92%
“…Figure 4 depicts daily DMI and daily methane production data from 220 cows from eight experiments using Holstein-Friesian cows (Grainger et al 2008b;2010a;Moate et al 2013;Williams et al 2013;Deighton et al 2014b; and three unpublished experiments, using the same methodology). The cows were at different stages of lactation and were fed a wide variety of diets containing in excess of 70% forage (pasture, pasture hay, pasture silage, or lucerne hay) and between 0% and 30% cereal grain (barley or wheat), with none of these diets containing any known methane mitigants.…”
Section: Modelling Enteric Methane Productionmentioning
confidence: 99%